A novel method for the remote condition assessment of buried pipelines using low-frequency axisymmetric waves. (September 2016) - Muggleton, J M; Rustighi, E
Abstract: "Mapping the Underworld" is a large multi-disciplinary, multi-university research programme taking place in the UK, which aims to revolutionize the way we undertake streetworks. Within this programme, a number of vibration-based techniques for remotely detecting and locating buried pipes have been developed. Relying either on the direct excitation of a pipe as it comes up to the surface or excitation of the ground in the vicinity of a buried pipe, mapping the ground surface vibration response allows information to be gathered concerning the pipe's exact position. However, contained within this surface response is often information which could, if utilized appropriately, provide insights into the condition of the pipe as well as its location. Furthermore, critical information regarding the condition of the ground in which a pipe is buried could, in some circumstances, be gleaned. In this paper, how this additional information might be extracted, used and eventually exploited is explored. Providing the basis for work currently being undertaken in a new programme, "Assessing the Underworld", example results are presented which demonstrate the immense potential of the proposed methods.